2015
DOI: 10.1001/jamaoto.2015.0659
|View full text |Cite
|
Sign up to set email alerts
|

Primary Surgery vs Chemoradiation Treatment of Advanced-Stage Hypopharyngeal Squamous Cell Carcinoma

Abstract: Patients with advanced-stage HP SCC treated surgically with adjuvant RT or CRT showed a trend toward clinically improved OS and RFS compared with patients treated with definitive CRT. However, the difference was not statistically significant, and further investigation with larger controlled trials using modern approaches should be undertaken to optimize the initial management of advanced-stage HP SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 27 publications
1
35
3
4
Order By: Relevance
“…Se analizó el beneficio de la quimioterapia para cada localización en la supervivencia global, observándose en el grupo de tumores de hipofaringe que la supervivencia a los 5 años era un 3,9 % mejor en aquellos pacientes que habían recibido quimioterapia concomitante. 20 Se han publicado estudios no aleatorizados, algunos específicos en cánceres de la laringe, otros de la hipofaringe [21][22][23][24] y otros mezclando cánceres de laringe e hipofaringe 25,26 . Beauvillain et al 21 compararon los resultados del tratamiento conservador frente a la cirugía radical en tumores resecables de hipofaringe; establecieron dos grupos, el primero tratado con quimioterapia de inducción seguida de cirugía radical con radioterapia postoperatoria y el segundo tratado con quimioterapia de inducción seguida de radioterapia.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Se analizó el beneficio de la quimioterapia para cada localización en la supervivencia global, observándose en el grupo de tumores de hipofaringe que la supervivencia a los 5 años era un 3,9 % mejor en aquellos pacientes que habían recibido quimioterapia concomitante. 20 Se han publicado estudios no aleatorizados, algunos específicos en cánceres de la laringe, otros de la hipofaringe [21][22][23][24] y otros mezclando cánceres de laringe e hipofaringe 25,26 . Beauvillain et al 21 compararon los resultados del tratamiento conservador frente a la cirugía radical en tumores resecables de hipofaringe; establecieron dos grupos, el primero tratado con quimioterapia de inducción seguida de cirugía radical con radioterapia postoperatoria y el segundo tratado con quimioterapia de inducción seguida de radioterapia.…”
Section: Discussionunclassified
“…Harris et al 23 , presentan una supervivencia mayor en pacientes con tumores de hipofaringe tratados con cirugía radical respecto la quimiorradioterapia, aunque estos resultados no fueron estadísticamente significativos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Furthermore, a study of the National Cancer Database showed that total laryngectomy led to a significantly better overall survival rate than did chemoradiotherapy for laryngeal preservation in patients with T4a laryngeal cancer (19). Harris et al retrospectively compared primary surgery followed by radiotherapy to definitive radiotherapy in locally advanced hypopharyngeal cancer, including 82% with stage IV (20). Primary surgery followed by radiotherapy tended to improve the overall survival rate compared with that of definitive radiotherapy (p=0.06).…”
Section: Discussionmentioning
confidence: 99%
“…Resultado similar obtienen Masegoza Zapata (117) y otros estudios (120,129,154), algunos basados en el cáncer supraglótico (73).…”
Section:  Comparación De Las Curvas De Supervivencia Por Estadiaje (unclassified